Screening of Toddler Development in Working Area of Community Health Center South Jakarta - Febry Mutiariami Dahlan; Shinta Novelia (Rajaki of Tulip Medika Publisher, 2026)
Monitoring the growth and development of toddlers is an important effort to improve children's health from an early age. Community health centers (Puskesmas), as primary healthcare facilities, play a strategic role in monitoring child development through posyandu activities and maternal and child health services. However, several challenges remain in its implementation. These include limited parental knowledge regarding the importance of regular child development monitoring, the limited capacity of posyandu cadres to conduct early developmental screening, and suboptimal systems for recording child development. These conditions may result in developmental delays not being detected at an early stage. This community service activity aims to improve the quality of child development monitoring at community health centers by enhancing the capacity of healthcare workers and posyandu cadres, strengthening the child development recording system, and increasing parental knowledge regarding age-appropriate child development stimulation. The solutions offered through this activity include training healthcare workers and posyandu cadres in the early detection of toddler growth and developmental problems, developing and implementing a more systematic child development monitoring system, and providing education to parents regarding age-appropriate child development stimulation. In addition, assistance will be provided in implementing child development monitoring activities at posyandu. The targeted outcomes of this activity include improved capacity among healthcare workers and posyandu cadres to conduct child developmental screening, the availability of a more structured child development recording system, increased parental knowledge regarding child development stimulation, and an increased number of children receiving regular developmental monitoring. Through this activity, it is expected that developmental delays in children can be detected more effectively and at an earlier stage, thereby supporting optimal child growth and development.